The cultures of ancient Xinjiang, western China : crossroads of the Silk Roads - Betts, A. V. G.,; Vicziany, Marika,; Jia, Weiming,; Di Castro, Angelo Andrea, (Archaeopress archaeology., 2019)
One of the least known but culturally rich and complex regions located at the heart of Asia, Xinjiang was a hub for the Silk Roads, serving international links between cultures to the west, east, north, and south. Trade, artefacts, foods, technologies, ideas, beliefs, animals, and people traversed the glacier covered mountain and desert boundaries. This book unveils the ancient secrets of Xinjiang, western China, one of the least known but culturally rich and complex regions located at the heart of Asia.